Differences between lipid content and composition of different parts of fillets from crossbred farmed carp (Cyprinus carpio) - Mráz, J; Pickova, J (Fish physiology and biochemistry, 2009)
Common carp (Cyprinus carpio) is, globally, one of the most important farmed fish species. We have analyzed carp from a natural pond-production system in South Bohemia. Ongrowing fish had access to an abundant plankton population which was supplemented with cereals. Fatty acid composition (FA) was investigated in three parts of fillets from four crosses of carp. The FA composition of the leanest part, the dorsal white muscle was similar to that of marine-farmed species; it contained a large proportion of n-3 highly unsaturated FA, the n-3/n-6 ratio was 1.1, and the proportion of phospholipids was high. The abdominal wall is rich in monounsaturated FA, the n-3/n-6 ratio is lower, 0.5, and it is more affected by the cereal feed. We concluded that the lipid composition of all these carp tissues can be improved in terms of healthy FA profile.
Keywords: Analysis of Variance; Animals; kosterní svaly; Chromatography, Gas; kapři; lipidy; chromatografie na tenké vrstvě; maso; vodní hospodářství; Meat; Lipids; Muscle, Skeletal; Aquaculture; křížení genetické; analýza rozptylu; Czech Republic; chromatografie plynová; Crosses, Genetic; Carps; Česká republika; zvířata; Chromatography, Thin Layer